A kinetics modeling study on the inhibition of glucose on cellulosome of Clostridium thermocellum. (August 2015) - Zhang, Pengcheng; Wang, Buyun; Xiao, Qunfang; Wu, Shan
Highlights: A kinetics model was built to study the inhibition of glucose on cellulosome. An experiment was built to verify the kinetics model. Glucose was proven to be an inhibitor for cellulosome by kinetics study. Parameters in model were discussed. Adsorbent for glucose could enhance cellulose hydrolysis. Abstract: A simplified kinetics model was built to study the inhibition of glucose on cellulosome of Clostridium thermocellum . Suitable reaction conditions were adopted to evaluate the model. The model was evaluated at different temperatures and further with various activated carbon additions as adsorbent for glucose. Investigation results revealed that the model could describe the hydrolysis kinetics of cellulose by cellulosome quite well. Glucose was found to be an inhibitor for cellulosome based on the kinetics analysis. Inhibition increased with the increase in temperature. Activated carbon as adsorbent could lower the inhibition. Parameters in the model were further discussed based on the experiment. The model might also be used to describe the strong inhibition of cellobiose on cellulosome. Saccharification of cellulose by both cellulosome and C. thermocellum could be enhanced efficiently by activated carbon addition.